“DAILY LIFE IN THE VILLAGE COURTYARD: ARTISTIC REPRESENTATIONS IN WORLD GENRE PAINTING” - Alimova Dinara Namozovna, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article examines how daily life in village courtyards has been portrayed in world genre painting. The study focuses on how artists represent everyday activities, social interactions, and natural surroundings through composition, color, and light. By analyzing the works of notable European and Russian painters, the article demonstrates that village courtyard scenes serve both aesthetic and cultural functions. They preserve social norms, historical context, and human interaction with nature, providing insight into rural life across various periods and regions